2022
DOI: 10.1186/s12985-022-01816-z
|View full text |Cite
|
Sign up to set email alerts
|

First description of a multisystemic and lethal SARS-CoV-2 variant of concern P.1 (Gamma) infection in a FeLV-positive cat

Abstract: Background Phylogenetic studies indicate bats as original hosts of SARS-CoV-2. However, it remains unclear whether other animals, including pets, are crucial in the spread and maintenance of COVID-19 worldwide. Methods In this study, we analyzed the first fatal case of a SARS-CoV-2 and FeLV co-infection in an eight-year-old male cat. We carried out a clinical evaluation and several laboratory analyses. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Alpha variant was isolated from cats with clinical conditions of varying severity, from asymptomatic [ 62 ], mild disease, characterized by sneezing [ 63 ], to severe conditions characterized by dyspnea and fever [ 64 ] or acute myocarditis [ 65 ]. The SARS-CoV-2 Gamma variant was identified as a cause of death of a FeLV-positive cat presenting severe acute respiratory syndrome and lesions in several organs [ 66 ]. The Delta variant was isolated from three cats from Harbin [ 67 ] and from a cat with history of anorexia, lethargy, soft stools, and vomiting [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha variant was isolated from cats with clinical conditions of varying severity, from asymptomatic [ 62 ], mild disease, characterized by sneezing [ 63 ], to severe conditions characterized by dyspnea and fever [ 64 ] or acute myocarditis [ 65 ]. The SARS-CoV-2 Gamma variant was identified as a cause of death of a FeLV-positive cat presenting severe acute respiratory syndrome and lesions in several organs [ 66 ]. The Delta variant was isolated from three cats from Harbin [ 67 ] and from a cat with history of anorexia, lethargy, soft stools, and vomiting [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found genetic disparity between two samples collected at different time points from cat BKK100 that had experienced chronic FeLV infection and suffered from kidney disease, suggesting the within-host evolution of SARS-CoV-2, which has been frequently observed in SARS-CoV-2 infection of immunocompromised patients ( 41 43 ). Thus, intrahost mutation of SARS-CoV-2 in immunocompromised cats is possible, as indicated by a previously reported observation of a SARS-CoV-2-infected immunocompromised cat ( 44 ). Furthermore, the rapid adaptation of SARS-CoV-2 variants to nonhuman mammalian hosts after initial infection with the original virus was reported ( 45 ), highlighting the potential of reinfection of humans with new variants arising in such animals that have close contact with humans.…”
Section: Discussionmentioning
confidence: 69%
“…If a cat is not treated in time, secondary infection can occur. A recent study showed that immunocompromised FeLV-positive cats are susceptible to SARS-CoV-2 infection [ 31 ]. At the current time of the coronavirus pandemic, it is possible that FeLV-positive cats act as a reservoir for new SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%